2008
DOI: 10.1177/147323000803600618
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Effects of Propofol on Human Cerebral Glucose Metabolism Using Positron Emission Tomography

Abstract: The effects of propofol on glucose metabolism in different cerebral regions were observed, using positron emission tomography (PET) technology, to determine a possible cerebral target region. Seven healthy volunteers were injected with 18 F-fluorodeoxyglucose developing agent for PET scanning whilst awake (control group T1), during sedation (induced by 1.5 µg/ml propofol administered by target controlled injection [TCI], group T2) and when unconsciousness (induced by 2.5 µg/ml propofol administered by TCI, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
5
18
0
Order By: Relevance
“…In a previous study, also using PET imaging, we observed in the subcortical regions, the decrease of glucose consumption in the thalamus was the largest, which is consistent with another PET study (Sun et al, 2008). In the present study, we showed that in 5 of 10 subjects, the signals of thalamus were decreased during propofol anesthesia although the changes were weak and significantly different compared with the changes in hypothalamus, frontal lobe, and temporal lobe.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, also using PET imaging, we observed in the subcortical regions, the decrease of glucose consumption in the thalamus was the largest, which is consistent with another PET study (Sun et al, 2008). In the present study, we showed that in 5 of 10 subjects, the signals of thalamus were decreased during propofol anesthesia although the changes were weak and significantly different compared with the changes in hypothalamus, frontal lobe, and temporal lobe.…”
Section: Discussionsupporting
confidence: 92%
“…Further, in the human brain, isoflurane (0.5% expired) has been shown to reduce CMRglu by 46% (Alkire et al, 1997). Propofol administered in concentrations inducing unconsciousness in humans also reduced CMRglu by B50% (Sun et al, 2008). Although much information has been gained from positron emission tomography studies in the live brain, it is important to acknowledge, that CMRglu measured by 2-deoxy-2-( 18 F)fluoro-D-glucose is interpreted as an indirect measure of neuronal function, and only provides information on the rate of glycolysis under the assumption of oxidative phosphorylation (Fowler and Ido, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…The effects of general anesthetics on traditional measures of brain function and metabolism, including the cerebral metabolic rate of glucose utilization (CMRglu), oxygen utilization, and neurotransmission, have been well characterized in humans and animals using jugular bulb oximetry, positron emission tomography, magnetic resonance imaging, or autoradiography (Alkire et al, 1995;Newberg et al, 1983;Olsen et al, 1992;Ori et al, 1986;Sun et al, 2008). For example, cortical oxidative metabolism and glutamate (Glu) flux have been shown to be stoichiometrically related, coupled to neuronal firing, and dependent on depth of barbiturate anesthesia (Shulman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography of adult human brains corroborated that propofol shifted central nervous system metabolism toward glycolysis. 10 However, those studies used 2-fluorodeoxyglucose uptake, and did not determine the actual fate of glucose. Similarly, other studies have used metabolic profiling by 1 H-nuclear magnetic resonance (NMR) to demonstrate differences between volatile anesthetics and propofol.…”
Section: Introductionmentioning
confidence: 99%